Interatrial block as a predictor of atrial fibrillation in patients with ST‐segment elevation myocardial infarction. Issue 9 (20th September 2018) - Çinier, Göksel; Tekkeşin, Ahmet İlker; Genç, Duygu; Yıldız, Ufuk; Parsova, Emrecan; Pay, Levent; Alexander, Bryce; Bozbeyoğlu, Emrah; Türkkan, Ceyhan; Alper, Ahmet Taha; Baranchuk, Adrian
Abstract : Introduction: Interatrial block (IAB) is strongly associated with recurrence of atrial fibrillation (AF) in different clinical scenarios. Atrial fibrosis is considered the responsible mechanism underlying the pathogenesis of IAB. The aim of this study was to investigate whether IAB predicted AF at 12 months follow‐up in a population of patients with ST segment elevation myocardial infarction (STEMI). Hypothesis: We aimed to investigate whether IAB predicted AF at 12 months follow up in a population of patients with STEMI. Methods: Prospective, single center, observational study of patients presenting with ST‐segment elevation myocardial infarction (STEMI) and referred to primary percutaneous coronary intervention (P‐PCI). Surface electrocardiograms (ECG) were recorded on admission and at 6th hour post P‐PCI. Patients were screened for the occurrence of AF at a 12‐months visit. Results: A total of 198 patients were included between September 2015 and September 2016. IAB (partial and advanced) was detected in 102 (51.5%) patients on admission. Remodeling of the P‐wave and subsequent normalization reduced the prevalence of IAB to 47 (23.7%) patients at 6th hour. AF was detected in 17.7% of study patients at 12 months. Partial IAB (p‐IAB) on admission (OR 5.10; 95% CI, 1.46‐17.8; P = 0.011) and on 6th hour (OR 4.15; 95% CI, 1.29‐13.4; P = 0.017), presence of a lesion in more than one coronary artery (OR 3.29; 95% CI, 1.32‐8.16; P = 0.010) found to be independent predictors of AF at 12 months. Conclusion: IAB is common in patients with STEMI and along with the presence of diffuse coronary artery disease is associated with new onset of AF.